HUBUNGAN LAMA PENGGUNAAN KONTRASEPSI SUNTIK DENGAN TEKANAN DARAH PADA WANITA USIA SUBUR DI KLINIK PRATAMA WIPA - Sinurat, Lasma Rina Efrina; Parapat, Friska Margareth (Jurnal Ilmiah Keperawatan, 2020)
Hormonal contraception is a method of contraception that has high effectiveness and is the most frequently used. Contraceptives, especially hormonal contraception, besides being able to cause changes in body weight are also dense causing an increase in blood pressure. Changes in high blood pressure can occur in 5% of hormonal contraceptive use, this is because many women of childbearing age use injectable contraceptives for a long time. The purpose of this study was to determine the relationship between the length of use of injectable contraceptives and blood pressure at the Wipa Clinic Pratama Medan. The research design used correlation analytic with cross sectional approach. The population of this study were all women of childbearing age who used injectable contraception. The sample of this study was 75 people, with a sampling technique that was simple random sampling. Collecting data with a questionnaire sheet. This study uses Chi square statistical test with CI = 95% and 0.05. The results of the study were the majority of injectable contraceptive use was 2 years (65.3%) and the majority of maternal blood pressure was high (130/80mmHg) (52%) based on the results of the chi-square statistical test with p value = 0.006. There is a long-standing relationship between the use of injectable contraceptives and blood pressure at the Wipa Pratama Clinic. It is recommended for women of childbearing age to increase knowledge about contraception used and often do counseling with health workers.